Exploring fatty acid metabolism in Alzheimer’s disease: the key role of CPT1A - Yanxiu Ju; Songtao Li; Xiangyi Kong; Qing Zhao (Scientific Reports)
Abstract Alzheimer’s disease (AD) is a severe neurodegenerative disease, and the most common type of dementia, with symptoms of progressive cognitive dysfunction and behavioral impairment. Studying the pathogenesis of AD and exploring new targets for the prevention and treatment of AD is a very worthwhile challenge. Accumulating evidence has highlighted the effects of fatty acid metabolism on AD. In this study, fatty acid metabolism was used as an entry point to understand the pathogenesis of AD and identify new targets. After identifying differentially expressed genes, multiple machine learning algorithms, carnitine palmitoyltransferase 1 A (CPT1A) was identified as the key gene for fatty acid metabolism in AD. Further single nucleus RNA sequencing analysis were performed, and the GSEA results showed that the fatty acid β-oxidation pathway was enriched only in astrocytes, and the fatty acid β-oxidation pathway was down-regulated in the AD astrocytes compared to the CN astrocytes, while CPT1A was specifically downregulated in astrocytes of AD, which was confirmed in vitro experiment subsequently, and decreased expression level of CPT1A would lead to abnormal lipid metabolism, which shapes astrocyte reactivity and injury, neuroinflammatory, and thus affects AD pathogenesis. Our findings report the involvement of CPT1A in AD. We confirm that the primary role of astrocytes for fatty acid β-oxidation, and CPT1A is localized in astrocytes. Downregulated CPT1A could be a novel potential target for the prevention and treatment of AD. Our study provides strong evidence for the involvement of fatty acid metabolism in the pathogenesis of AD.